IMPLEMENTASI SISTEM INFORMASI AKUNTANSI HARGA POKOK PESANAN PADA CV CITRA INDAH FURNITURE PITURUH PURWOREJO - , (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2020)
CV Citra Indah Furniture is a manufacturing company that produces furniture such as desks, chairs, cabinets, and others upon request. In the processing of raw materials into finished products are called the cost with the cost of production. Production costs are attached to the product will be taken into account in determining the cost of each product order. The calculation cost of the order is necessary to determine the selling price, accept or reject the order, monitoring the actual production costs, calculate the profit or loss orders, and determining the cost of inventories of finished products. In the operations, CV Citra Indah Furniture does not have any record in to bookkeeping so that there has been no order cost calculation which takes into account the elements of production costs inherent in each product order. This can make not valid to determining the selling price that the exact result in the profit or loss generated. To overcome this problem we need a system of order cost accounting information using Microsoft Excel 2007. System order cost accounting information on CV Citra Indah Furniture Pituruh using Microsoft Excel 2007 to discuss the allocation of manufacturing overhead costs and manufacturing overhead rate calculation, transaction journals, general ledger, a recapitulation of the actual factory overhead cost, order cost card, report the cost sales, and income statement. Applications using Microsoft Excel 2007 is more effective and easy to use to the books and the calculation of the order cost. Keywords: accounting information systems, order cost